Management of kyphoscoliosis patients with respiratory failure in the intensive care unit and during long term follow up - Adıgüzel Nalan (Multidisciplinary Respiratory Medicine, 2012)
Abstract Background We aimed to evaluate the ICU management and long-term outcomes of kyphoscoliosis patients with respiratory failure. Methods A retrospective observational cohort study was performed in a respiratory ICU and outpatient clinic from 2002–2011. We enrolled all kyphoscoliosis patients admitted to the ICU and followed-up at regular intervals after discharge. Reasons for acute respiratory failure (ARF), ICU data, mortality, length of ICU stay and outpatient clinic data, non-invasive ventilation (NIV) device settings, and compliance were recorded. NIV failure in the ICU and the long term effect of NIV on pulmonary performance were analyzed. Results Sixty-two consecutive ICU kyphoscoliosis patients with ARF were enrolled in the study. NIV was initially applied to 55 patients, 11 (20%) patients were intubated, and the majority had sepsis and septic shock (p < 0.001). Mortality in the ICU was 14.5% (n = 9), reduced pH, IMV, and sepsis/septic shock were significantly higher in the non-survivors (p values 0.02, 0.02, 0.028, 0.012 respectively). Among 46 patients attending the outpatient clinic, 17 were lost to follow up and six were died. The six minute walk distance was significantly increased in the final follow up (306 m versus 419 m, p < 0.001). Conclusions We strongly discourage the use of NIV in the case of septic shock in ICU kyphoscoliosis patients with ARF. Pulmonary performance improved with NIV during long term follow up.